2019
DOI: 10.1002/humu.23842
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of BRCA1 and BRCA2 pathogenic sequence variants in Middle Eastern, North African, and South European countries

Abstract: BRCA1 BRCA2 mutational spectrum in the Middle East, North Africa, and Southern Europe is not well characterized. The unique history and cultural practices characterizing these regions, often involving consanguinity and inbreeding, plausibly led to the accumulation of population‐specific founder pathogenic sequence variants (PSVs). To determine recurring BRCA PSVs in these locales, a search in PUBMED, EMBASE, BIC, and CIMBA was carried out combined with outreach to researchers from the relevant countries for un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 37 publications
(71 reference statements)
2
33
0
Order By: Relevance
“…Establishing the mutational profile in our region will allow directed testing of high-risk families, therefore increasing the benefit while reducing costs. This is an agreement with Laitman et al who identified several highly-recurring mutations in the region 13 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Establishing the mutational profile in our region will allow directed testing of high-risk families, therefore increasing the benefit while reducing costs. This is an agreement with Laitman et al who identified several highly-recurring mutations in the region 13 .…”
Section: Discussionsupporting
confidence: 93%
“…Recently, a comprehensive assessment of the mutational spectrum of BRCA1 / BRCA2 in the Middle East, North Africa, and Southern Europe was published 13 . Laitamn et al reported recurring pathogenic sequence variants (PSVs) identifying 232 PSVs and 239 PSVs in BRCA1 and BRCA2 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In BRCA1gene, we identi ed the c.5030_5033delCTAA mutation in 3 out of 15 (20%) unrelated patients with early onset familial. This mutation has not been reported in North Africa but was found in patients from Greece, Italy, Jordan, Lebanon, Kuwait, and Saudia Arabia [15]. In addition, the nonsens mutation c.2338C > T was shared by 2 young patients (< 50 years-old) diagnosed with ovarian cancer.…”
Section: Discussionmentioning
confidence: 80%
“…BRCA1 and BRCA2 have key roles in the development of breast/ovarian cancer [9,10]. The prevalence of BRCA1/BRCA2 mutations varies in different populations due to founder mutation effect [15,[24][25][26][27][28]. Genetic testing of patients with family history for breast/ovarian cancer have become standard clinical management in Western countries, however, in Tunisia studies of BRCA-associated breast/ovarian cancer remain less investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation